MiR‐126‐5p enhances radiosensitivity of lung adenocarcinoma cells by inhibiting EZH2 via the KLF2/BIRC axis. Issue 9 (24th March 2022) - Han, Fushi; Huang, Dongdong; Meng, Jinqian; Chu, Jiapeng; Wang, Meng; Chen, Shuzhen
Abstract: Radiotherapy is a common method for the treatment of lung adenocarcinoma, but it often fails due to the relative non‐susceptibility of lung adenocarcinoma cells to radiation. We aimed to discuss the related mechanisms by which miR‐126‐5p might mediate radiosensitivity of lung adenocarcinoma cells. The binding affinity between miR‐126‐5p and EZH2 and between KLF2 and BIRC5 was identified using multiple assays. A549 and H1650 cells treated with X‐ray were transfected with miR‐126‐5p mimic/inhibitor, oe‐EZH2, or si‐KLF2 to detect cell biological functions and radiosensitivity. Finally, lung adenocarcinoma nude mouse models were established. miR‐126‐5p and KLF2 were poorly expressed, while EZH2 and BIRC5 were upregulated in lung adenocarcinoma tissues and cells. miR‐126‐5p targeted EZH2 to promote the KLF2 expression so as to inhibit BIRC5 activation. Both in vitro and in vivo experiments verified that elevated miR‐126‐5p inhibited cell migration and promoted apoptosis to enhance the sensitivity of lung adenocarcinoma cells to radiotherapy via the EZH2/KLF2/BIRC5 axis. Collectively, miR‐126‐5p downregulated EZH2 to facilitate the sensitivity of lung adenocarcinoma cells to radiotherapy via KLF2/BIRC5.